Rich quasiparticle properties of low dimensional systems - Lin, Chiun-Yan; Yang, Cheng-Hsueh; Chiu, Chih-Wei; Chung, Hsien-Ching; Lin, Shih-Yang; Lin, Ming-Fa (IOP ebooks. [2021 collection], 2021)
This book discusses the essential properties of carbon nanotubes and 2D graphene systems. The book focuses on the fundamental excitation properties of a large range of graphene-related materials, presenting a new theoretical framework that couples electronic properties and e-e Coulomb interactions together in order to thoroughly explore Coulomb excitations and decay rates in carbon-nanotube-related systems